Economic analysis of smallholder dairy cattle enterprises in Senegal - Malenje, E.M.; Missohou, A.; Tebug, S.F.; König, E.Z.; Jung’a, J.O.; Bett, R.C.; Marshall, Karen (Springer, 2022)
Smallholder dairy production in Senegal is important to both livelihoods and food and nutrition security. Here, we examine the economic performance of smallholder dairy cattle enterprises in Senegal, using data from longitudinal monitoring of 113 households. The mean (and standard deviation) of the net returns (NR) per cow per annum (pcpa) was 21.7 (202.9) USD, whilst the NR per household herd per annum (phpa) was 106.1 (1740.3) USD. Only about half (52.2%) of the dairy cattle enterprise had a positive NR. The most significant income components were milk sale followed by animal sale, whilst the most significant cost components were animal feed followed by animal purchase. When households were grouped by ranking on NRpcpa, an interesting trend was observed: whilst the mean NRpcpa showed a fairly linear increase from the lowest to highest NR groups, income and cost did not. Income and costs were both higher for the lowest and highest NR groups, in comparison to the intermediate NR groups. The mean NRs of households grouped by the main breed type they kept were not significantly different from each other, due to large variances within the breed groups. However, the mean total income and costs were significantly higher for households mainly keeping improved dairy breeds (Bos taurus or Zebu × Bos taurus crosses) in comparison to those keeping indigenous Zebu or Zebu by Guzerat crosses. This study highlights the highly variable (and often low) profitability of smallholder dairy cattle enterprise in Senegal. Further actions to address this are strongly recommended.